Variable, fixed, and hybrid sampling period approach for grid synchronization - Carugati, Ignacio (2017)
Almost all synchronization methods that can be found in the literature are based on a fixed sampling period approach and implemented by the addition of filter stages to the conventional Synchronous Reference Frame Phase Locked Loop (SRF-PLL) structure. A less common approach is the variable sampling period (VSP), used in methods like VSP-PLL. These methods allow implementing a synchronous sampling period which automatically adapts the monitoring and control systems to the grid voltage and current, improving their processing performance. Notwithstanding the advantages of the synchronous sampling period approach, this operation principle is not commonly adopted in the literature since a proper design is required to avoid implementation problems and possible conflicts with other modules. This manuscript reviews the advantages of VSP approach, unveils similarities between VSP-PLL and SRF-PLL that allow improving the understanding of the former by comparing it to the latter, and provides guidelines for a proper implementation of a synchronous sampling method. In addition, a Hybrid Sampling Period (HSP) approach that combines the advantages of SRF-PLL and VSP-PLL is proposed. The three approaches are compared, the advantages of hybrid methods are discussed and the methodology for adopting the VSP and HSP approach in most fixed sampling period method is presented. Finally, the proposal is verified by experimental implementation.